Consumptive qualities of different potato varieties - М. М. Фурдига; Ю. Я. Верменко; Т. Д. Сонець (Plant Varieties Studying and Protection)
Purpose. To summarize results of studying consumptive qualities of different varieties of potato and define basic characteristics which allow to subsume them under specific economic categories.